2002
DOI: 10.1183/09031936.02.00249302
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of inhaled nitric-oxide induced reduction of pulmonary artery pressure and vascular changes

Abstract: The purpose of the present study was to determine the relationship between hypertensive pulmonary vascular remodelling and the changes in mean pulmonary artery pressure (mPAP) during low-dose nitric oxide (NO) inhalation.Rats were exposed to chronic hypobaric hypoxia (air at 50.5 kPa (380 mmHg), 10% oxygen, for 5-29 days) to induce chronic pulmonary hypertension (PH) with pulmonary vascular structural changes. After the chronic hypoxic exposure, the rats had an indwelling pulmonary artery catheter inserted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Commercially available computer software was used to incrementally increase pressure every 1.38 kPa. A review of the literature showed that mean pulmonary arterial pressure (mPAP) in healthy rats can range from 2.57 kPa (Jiang et al, 2002) in Sprague-Dawley rats to 3.84 kPa (Deten et al, 2003) in Long-Evans rats. A maximum inflation pressure of 17.9 kPa was chosen to mimic extreme hypertension in the pulmonary artery.…”
Section: Methodsmentioning
confidence: 99%
“…Commercially available computer software was used to incrementally increase pressure every 1.38 kPa. A review of the literature showed that mean pulmonary arterial pressure (mPAP) in healthy rats can range from 2.57 kPa (Jiang et al, 2002) in Sprague-Dawley rats to 3.84 kPa (Deten et al, 2003) in Long-Evans rats. A maximum inflation pressure of 17.9 kPa was chosen to mimic extreme hypertension in the pulmonary artery.…”
Section: Methodsmentioning
confidence: 99%
“…Under normoxic conditions, inhaled NO has little vasodilatory effect on the adult pulmonary vasculature, suggesting perhaps a maximally vasodilated state at baseline or a non-responsiveness to NO (Jiang et al, 2002; Koizumi et al, 1994; Pison et al, 1993). In models of hypoxia-, thromboxane-, or endotoxin-induced pulmonary hypertension or acute lung injury associated pulmonary hypertension, NO blunts vasoconstriction and lowers pulmonary arterial pressure (Bottiger et al, 1996; Frostell et al, 1993; Rich et al, 1993; Rossaint et al, 1993; Weitzberg et al, 1993).…”
Section: Pathophysiological Role Of Cgmp Signaling In Cardiovasculamentioning
confidence: 99%
“…27 An aortic catheter was also passed from the left carotid artery into the ascending aorta to measure arterial pressure. At 24 to 48 hours after the catheterization and under conscious conditions in which the animals were calm and free-moving, a single oral administration of fasudil (3, 10, and 30 mg/kg) or vehicle was performed, and hemodynamic variables were continuously monitored with a polygraph system (AP-601G; Nihon Kohden, Tokyo, Japan) before and after the fasudil administration at 0.5, 1, 3, 5, 7, and 24 hours.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%